Analysis of tidal accelerations in the solar system and in extrasolar planetary systems - Paschek, Klaus; Roßmann, Arthur; Hausmann, Michael; Hildenbrand, Georg Lars (Applied Sciences, 2021)
Volcanism powered by tidal forces inside celestial bodies can provide enough energy to keep important solvents for living systems in the liquid phase. A prerequisite to calculate such tidal interactions and consequences is depending on simulations for tidal accelerations in a multi-body system. Unfortunately, from measurements in many extrasolar planetary systems, only few physical and orbital parameters are well-known enough for investigated celestial bodies. For calculating tidal acceleration vectors under missing most orbital parameter exactly, a simulation method is developed that is only based on a few basic parameters, easily measurable even in extrasolar planetary systems. Such a method as the one presented here allows finding a relation between the tidal acceleration vectors and potential heating inside celestial objects. Using the values and results of our model approach to our solar system as a “gold standard” for feasibility allowed us to classify this heating in relation to different forms of volcanism. This “gold standard” approach gave us a classification measure for the relevance of tidal heating in other extrasolar systems with a reduced availability of exact physical parameters. We help to estimate conditions for the identification of potential candidates for further sophisticated investigations by more complex established methods such as viscoelastic multi-body theories. As a first example, we applied the procedures developed here to the extrasolar planetary system TRAPPIST-1 as an example to check our working hypothesis.
Gesehen am 20.10.2021